Desenvolvimento de um escore clínico de sepse murina e sua aplicação na avaliação do efeito da eHSP72 e anticorpo para HSP70 em camundongos envelhescentes - Sulzbacher, Maicon Machado (2024)
Introduction: Sepsis is a microbial infection with systemic dysfunctions, more severe in older individuals (due to biological changes). These dysfunctions involve oxidative stress and modulation of the cytoprotective expression of intracellular 70kDa heat shock protein (iHSP70) and its interaction with immune cells in the extracellular environment (eHSP72). Intravenous treatment with eHSP72 reduced the severity of sepsis in young adult mice. However, the administration and neutralization of these proteins in aging animals have not yet been investigated. In studies with murine models, it is relevant to evaluate other sepsis markers beyond those used in the Murine Sepsis Score (MSS), which is based on the assessment of certain characteristics. Objectives: To develop a murine sepsis score that includes physiological markers (Article) and to evaluate the effects of eHSP72 and anti-HSP70 administration in aging mice (Manuscript). Methodology: In the Article, 15 young adult mice were used, subjected to sepsis (intraperitoneal injection of fecal solution) and evaluated using the MSS, body temperature, weight loss, and blood glucose over 24 hours. In the Manuscript, 32 aging mice were used, divided into four groups: control (CONT), sepsis (SEP), sepsis with the intervention (at 12 hours) of eHSP72 (SEP+eHSP72), and anti-HSP70 (SEP+Anti-HSP70), evaluated using the Adapted Murine Sepsis Score (A-MSS), blood count, respiratory rate, oxidative stress (liver, heart, and lungs), cholesterol, and triglycerides (liver). Results: The first study, published in the journal BioMed Research International, included additional physiological parameters in the MSS instrument, allowing for a more accurate assessment of sepsis. This set of results supported the proposal of an evaluation tool for sepsis called the Adapted Murine Sepsis Score (A-MSS). This tool indicated sepsis severity earlier and more comprehensively in mice, potentially being relevant for studies evaluating other sepsis-related markers. In the Manuscript, animals with sepsis showed an increase in the A-MSS. The survival rate in the SEP group dropped to 75%, while in the intervention groups, it dropped to 67% (SEP+eHSP72) and 60% (SEP+Anti-HSP70). Hypothermia indicated worsening and mortality in all groups. No changes were observed in the activity of SOD, lipid peroxidation, or iHSP70 expression in any of the analyzed tissues. Sepsis decreased respiratory rate. Interventions with eHSP72 and anti-HSP70 impaired hepatic and pulmonary CAT activity. SEP and SEP+eHSP72 increased the NLR throughout the study, while SEP+Anti-HSP70 decreased it compared to SEP and increased AISI and SIRI indices (vs. its time 0). Circulating eHSP72 decreased in SEP, indicating severity, although the ratio between extracellular and intracellular concentrations of HSP70 (H Index) did not indicate tissue damage (lung and liver). Final considerations: The A-MSS identifies murine sepsis earlier and in a more complex manner. Intravenous interventions with eHSP72 and anti-HSP72 altered sepsis in aging mice, which may be related to a poorer response to the infectious challenge. Considerando resultados previamente descritos na literatura, os dados sugerem que a intervenção farmacológica com HSPs é influenciada pelo envelhecimento do animal.